The classification of potassium basaltic trachyandesites that were discharged by the 2012–2013 parasitic eruption on Ploskii Tolbachik Volcano, Kamchatka using geochemical criteria - Khubunaya S.A.; Eremina T.S.; Sobolev A.V. (Journal of Volcanology and Seismology, 2016)
Abstract—This study is concerned with the petrographic, mineralogic, and geochemical features in the K-high basaltic trachyandesites that were discharged by the 2012–2013 parasitic eruption on Ploskii Tolbachik Volcano. These K-high basaltic trachyandesites exhibit some obvious characteristics that testify to their suprasubduction origin. They are deeply differentiated rocks with strongly fractionated plagioclase.A study of the Sr, Nd, and Pb radiogenic isotope ratios in the K-high basaltic trachyandesites provided evidence of their mantle origin and of the fact that the crust has exerted no influence on their compositions. We performed a comparative analysis of the ratios of the concentrations for some incoherent elements in the K-high basaltic trachyandesites, as well as in intraplate, riftogenic, and island-arc moderate potassium basalts and basaltic andesites in relation to the concentrations of these elements in the primitive mantle. The geochemical features of these K-high basaltic trachyandesites classify them as belonging to the suprasubduction subalkaline formation of the potassium series.